OâMARK: INOVASI PEMANFAATAN PROSTAGLANDIN E2 DALAM SALIVA SEBAGAI EVALUASI TINGKAT KEPARAHAN PERIODONTITIS - Amelia, Fitri; Pustaka, Tiana; Irsyadi, Fahmi Tsani; Fitriana, Ardian Ayu; Seputraningrum, Yuliana; Rachmawati, Ranny (Program Kreativitas Mahasiswa - Penelitian, 2014)
Periodontitis is an inflammatory disease affects teeth supporting tissues which causing loss of periodontal attachment and damaging alveolar bone. Periodontitis trigger host to produce monocytes, polymorphonuclears (PMN), macrophages and others to release inflammatory mediators such as IL-1, TNF-Î±, PGE2. In periodontal disease, PGE2 role in breakdown of alveolar bone. The biomarker used PGE2 that contained in human saliva. This research aims to prove that PGE2 in saliva could be a new method to measure severity and early diagnosis of periodontitis. This research used Post Test Only Controlled Group Design with human saliva as the samples. The samples collected from 20 patients divided into two groups which are: control group (patient without periodontitis) and experimental group (patient with periodontitis). Saliva collecting method which used was Passive Drool with 2 ml for each. Afterwards, the samples isolated with a kit to make sure the PGE2 in saliva active and then the ELISA test did. Data analysis used Independent T Test with p<0,05 to know comparison the level of PGE2 in both groups. Thereafter, a ROC curve analysis with p<0,05 used to find out sensitivity and specifity of PGE2 in saliva towards periodontitis. The amount of PGE2 in saliva were significantly increased in periodontitis patients compared with healthy patients, also PGE2 in saliva specific enough and sensitive to periodontitis so its could be used as a valid diagnostic tool in measuring the severity of periodontitis.Â Keywords: Â Prostaglandin E2, saliva, periodontitis, early diagnose, severity